IMPLIKASI KEBIJAKAN MONETER TERHADAP STABILITAS PASAR MODAL DAN KINERJA SEKTOR KEUANGAN DI INDONESIA: SUATU KAJIAN PUSTAKA - Loso Judijanto; Riyadatul Muthmainnah; Ahmad Rizani (Berajah Journal, 2026)
Monetary policy is a fundamental instrument used by Bank Indonesia to maintain macroeconomic stability; however, its implications for capital market stability and the performance of the financial sector remain a complex and dynamic topic. This article aims to critically examine the implications of monetary policy for capital market stability and the performance of the financial sector in Indonesia through a literature review using a descriptive qualitative method. The findings indicate that monetary policy influences capital market stability through transmission channels involving interest rates, liquidity, inflation expectations, and foreign capital flows, with market responses tending to be asymmetric—where expansionary stimulus leads to a more significant rise in valuations compared to the pressure from policy tightening. Regarding the financial sector, particularly the banking sector, monetary policy exhibits multidimensional impacts: interest rate hikes can boost the Net Interest Margin (NIM) and profitability of large banks, yet may potentially lower credit quality (NPLs) and slow down credit growth. Harmonious policy coordination between Bank Indonesia, the OJK, and the Ministry of Finance through the Financial System Stability Coordination Forum (FKSSK) is a critical factor in mitigating systemic risks and ensuring the effectiveness of policy transmission. This study makes an academic contribution to the development of monetary and financial economics literature, as well as offering practical implications for policymakers and market participants in formulating strategies responsive to the monetary policy cycle to support stability and sustainable economic growth.